Master of Science in Information Science - Parthasarathy, S.; Neelameghan, A. (Journal of Information and Knowledge, 1978)
The factors contributing to the increasing demand for specialised manpower for developing, operating, and managing information systems and services are discussed. The development of NISSAT, NIC, R and D in Industries require adequate manpower in the information area. A training programme in M Sc in Information Science is suggested. The objectives, course of studies, duration, syllabus, and admission requirements are outlined.